2018
DOI: 10.1007/s13238-018-0532-9
|View full text |Cite
|
Sign up to set email alerts
|

Of genes and microbes: solving the intricacies in host genomes

Abstract: Microbiome research is a quickly developing field in biomedical research, and we have witnessed its potential in understanding the physiology, metabolism and immunology, its critical role in understanding the health and disease of the host, and its vast capacity in disease prediction, intervention and treatment. However, many of the fundamental questions still need to be addressed, including the shaping forces of microbial diversity between individuals and across time. Microbiome research falls into the classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 120 publications
(132 reference statements)
2
38
0
Order By: Relevance
“…Consequently, A. muciniphila can regulate the host's metabolism and immune function. However, the causal relationship between the microbes and host genomes is very complicated and needs to be further evaluated (Wang et al ., ,b).…”
Section: Colonization Of a Muciniphila And Its Interaction With The mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, A. muciniphila can regulate the host's metabolism and immune function. However, the causal relationship between the microbes and host genomes is very complicated and needs to be further evaluated (Wang et al ., ,b).…”
Section: Colonization Of a Muciniphila And Its Interaction With The mentioning
confidence: 99%
“…Consistently, Wang et al . (,b) reported one patient with high‐grade metastatic urothelial carcinoma showed immune checkpoint inhibitors (ICI)‐associated colitis after a trial of combined CTLA‐4 and PD‐1 blockade. After ICI‐associated colitis in the patient was successfully treated with FMT, donor‐derived bacteria were observed to be effectively colonized in the patient's intestinal tract, with an obviously higher level of A. muciniphila .…”
Section: Akkermansia Muciniphila Regulated the Balance Between Healthmentioning
confidence: 99%
“…While genetic effects on the gut microbiota have been detected in laboratory and human studies (Wang et al . ), these are often rather weak, and within‐species studies typically emphasise the strong influence of environmental factors, such as diet (Carmody et al . ; Rothschild et al .…”
Section: Introductionmentioning
confidence: 99%
“…Strong environmental effects have also been reported in studies of wild animals, including seasonal and habitat differences (Maurice et al 2015;Amato et al 2016;Ren et al 2017). While genetic effects on the gut microbiota have been detected in laboratory and human studies (Wang et al 2018), these are often rather weak, and within-species studies typically emphasise the strong influence of environmental factors, such as diet (Carmody et al 2015;Rothschild et al 2018;Weissbrod et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The human gut is home to tremendous amount of microbes[1]. They inhabit different ecological niches in the gut, forming complex interaction networks between themselves and with the human cells, and the dynamic balance between gut microbiome and host is required for human health[26]. Studies in human cohort and mouse models, among others, have confirmed that gut microbial communities are associated with increasing number of some of metabolism diseases and infectious diseases, providing insights as well as potential targets for future monitoring and therapies[3, 714].…”
Section: Introductionmentioning
confidence: 99%